Trans-popliteal hybrid retrograde technique for revascularization of chronic total occlusions of the superficial femoral artery. (August 2021) - García-Domínguez, Luis J; Falcón, Moisés; Ribé, Lucas; Hernández, Ana; Miralles, Manuel
Objectives: We present the technical description and preliminary results of a hybrid approach for the treatment of chronic total occlusions of superficial femoral artery in the setting of critical limb-threatening ischemia (CLTI). Methods: A retrospective analysis of selected case series was performed. A trans-popliteal hybrid technique was carried out in seven limbs (six patients). Open exposure of above-the-knee popliteal artery was performed over its maximum calcification zone. After retrograde recanalization and graft-stenting of the entire superficial femoral artery, endarterectomy of the popliteal artery was performed for debulking and widening of the distal landing zone of the endoprosthesis. The latter is included in the bovine patch suture to avoid leaving a segment untreated. Results: Technical success, haemodynamic and clinical improvement were achieved in all procedures. Median length of treated occlusion was 19.8 cm. After a mean follow-up of 12 months (range 6–26 months), the primary patency was 85.7% (only one asymptomatic occlusion occurred). There were no major cardiovascular or limb adverse events. No re-interventions were required. Conclusion: This less-invasive, one-incision technique is safe and effective for the restoration of in-line flow from groin to ankle, currently recommended in CLTI revascularization. It could be especially useful in highly calcified popliteal artery lesions, hostile groins or those at high risk of infection and in cases of vein absence for bypass surgery.